Coevolution and dependency influence resistance of mutualists to exploitation - Vidal, Mayra C.; Agarwal, Renuka; Segraves, Kari A. (Frontiers in Ecology and Evolution, 2024)
A long-standing problem in the study of mutualism is to understand the effects of non-mutualistic community members that exploit the benefits of mutualism without offering commodities in exchange (i.e., 'exploiters'). Mutualisms are continually challenged by exploiters and their persistence may depend on the costliness of exploitation or on adaptations that allow mutualists to avoid the negative effects of exploiters. Coevolution could lead to changes in mutualists and exploiters that allow mutualisms to persist. Although coevolution is considered essential for mutualism persistence and resistance to disturbance, we have yet to obtain direct experimental evidence of the role of coevolution in resistance to exploitation. Additionally, resistance to exploitation via coevolutionary processes might vary with the degree of dependency between mutualistic partners, as facultative mutualisms are thought to be under weaker coevolutionary selection than obligate mutualisms. Here, we conducted an experimental evolution study using a synthetic yeast mutualism to test how coevolution in facultative and obligate mutualisms affects their resistance to exploitation. We found that naïve facultative mutualisms were more likely to breakdown under exploitation than naïve obligate mutualisms. After 15 weeks of coevolution, both facultative and obligate evolved mutualists were more likely to survive exploitation than naïve mutualists when we reassembled mutualist communities. Additionally, coevolved exploiters were more likely to survive with mutualists, whereas naïve exploiters frequently went extinct. These results suggest that coevolution between mutualists and exploiters can lead to mutualism persistence, potentially explaining why exploitation is ubiquitous but rarely associated with mutualism breakdown.